2006
DOI: 10.1037/0022-006x.74.4.707
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of the relationship between symptoms and quality of life in veterans treated for posttraumatic stress disorder.

Abstract: This study examined how change in posttraumatic stress disorder (PTSD) symptoms relates to change in quality of life. The sample consisted of 325 male Vietnam veterans with chronic PTSD who participated in a randomized trial of group psychotherapy. Latent growth modeling was used to test for synchronous effects of PTSD symptom change on psychosocial and physical health-related quality of life within the same time period and lagged effects of initial PTSD symptom change on later change in quality of life. PTSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
153
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(180 citation statements)
references
References 29 publications
23
153
1
1
Order By: Relevance
“…In previous studies, psychosocial HRQoL was measured by role-emotional, social functioning, mental health, and fatigue subscales of SF-36. However, as suggested previously (Schnurr et al, 2006), there are spurious relationships between PCL and the mental health and fatigue subscales of the SF-36. Some items of the two subscales are very similar to PCL items.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…In previous studies, psychosocial HRQoL was measured by role-emotional, social functioning, mental health, and fatigue subscales of SF-36. However, as suggested previously (Schnurr et al, 2006), there are spurious relationships between PCL and the mental health and fatigue subscales of the SF-36. Some items of the two subscales are very similar to PCL items.…”
Section: Discussionsupporting
confidence: 60%
“…Our results also provide suggestions for clinical practice. According to clinical investigations, treatment for PTSD will lead to improvements in HRQoL (Aversa et al, 2013; Schnurr et al, 2006). Our results suggest that interventions targeting dysphoric arousal symptoms should be developed to improve quality of life among PTSD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, PTSD is associated with impairments in occupational and academic functioning [2][3][4][5][6], marital and family functioning [5,[7][8], parenting [9][10], and friendships and socializing [11]. Additional studies have shown associations between PTSD and objective indicators of quality of life (QOL) such as homelessness and unemployment [12][13]. Such impairments are common among populations at high risk for PTSD, such as military personnel deployed to combat [3,[5][6][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%